Rasgos morfológicos del fitoplancton en seis sistemas leníticos de las regiones Amazónica, Andina y Caribe de Colombia (2012)
ABSTRACT: We analyzed the morphological features of volume, maximum linear dimension, and area: volume ratio of phytoplankton assemblages of six lentic systems of different origin and morphology, including mountain lakes and oodplain lakes, all located in the Amazonian, Andean, or Caribbean regions of Colombia. In Colombia, studies of the structure of phytoplankton assemblages conducted from the viewpoint of morphological traits are scarce and those that have been conducted have favored high mountain lakes, was very few conducted in oodplain lakes. The objective of this study was to analyze the variability of morphological attributes and strategies of phytoplankton in six lentic systems. We found that in shallow, turbid, and warm environments, organisms were characterized by a high S/V, and presented mucilage and specialized traits such as agella, heterocites, and aerotopes: in contrast, in deep, clear, or lower temperature environments, phytoplankton predominated that were large and with few categorical or special traits, revealing morphological differences in assemblages of phytoplankton from systems in uenced by different sources, types, and hydroclimatology.